The Effect Of Prolonged Online Learning On Students’ Performance Post Locked Down During Covid-19 Pandemic - Bharwani, Vandena; ALi Mohammed, Lubna (Jurnal Multidisiplin Indonesia, 2023)
Many Schools, colleges and universities around the world suspended classroom teaching due to the novel Covid-19 Pandemic. Due to this, switching to online teaching has impacted students' performance, motivation and overall SEL skills. The current report was to analyze the impact of the COVID pandemic on Primary school students. By using survey data technique and analysed using quantitative research method, 41 participants whose parents participated and the children are in the range of grades 1-8; 85% -90% of the respondents saw a shift in motivation and performance behavior towards learning caused by online learning. The results showed that there is a significant impact on students motivation due to the differences in virtual learning (internet connection/ noise disruption/ other activity disruption/ gadgets/ people) in virtual learning from the home, resulting in lowering the quality of learning and curriculum covered. Monotonous and prolonged theory-based virtual learning effects on students' participation. Learning performance is decreased due to differences in virtual learning such as internet connection or the not-so-conducive environment for learning. Limitation of practical learning (physical activity) due to prolonged online learning leads to demotivation in learning. Affecting students’ performance, the SEL overall development is decreased due to the limitation of physical activity in prolonged online learning. Students' time management and discipline are affected due to the differences in the virtual learning environment. Students become demotivated due to limitations to physical learning resources in prolonged online learning. External motivation are missing in a prolonged virtual environment learning leading to demotivation. As a result, students feel stressed because of online learning, hence, the academic performance of students has been affected negatively, leading to a decline in their grades’ Learning performance is decreased due to limitations in learning resources requiring extra work or covering less content in an online environment. In conclusion, is deciphered that all parents and teachers would like their children to receive holistic learning at schools being in school and not from home.